System Programming in a High Level Language - Birrell, Andrew (1977)
This thesis is concerned with the construction of a high level language system suitable for the implementation of a general purpose operating system for a computer. There are three aspects to this task: firstly, a suitable high level language must be chosen or designed; secondly, a suitable implementation of this language must be manufactured; thirdly, the operating system itself must be written. These three aspects inevitably overlap in time - experience in implementing the language may cause one to review decisions taken in the design of the language, and experience in constructing the operating system will bring to light inadequacies, inconveniences and inelegancies in both the implementation and the language.
Ph.D. Thesis, University of Cambridge